The Effects of Blue and Red Light on Physiological Responses Post-Exercise - Cesarz, Taylor; Notermann, Sydney; Quirt, Cassandra; Rojo, Eric; Schotten, Hayley; Tarr, Shelby (Journal of Advanced Student Sciences (JASS), 2015)
The connection between color and rate of return to a resting physiological state post-exercise could lead to practical implementation in various fields, such as relaxation after strenuous activity. To measure this rate we focused on mean arterial blood pressure, pulse, and respiratory rate post-exercise in subjects placed in varying lighting conditions, which comprised of normal (white), red, and blue light. Based on limited previous research, we hypothesized that blue light would expedite recovery to resting levels, while red light would inhibit this return with white light implemented as a baseline control. The results suggest there is minimal significant correlative relationship between colored lighting conditions and a return to resting physiological rates post-exercise. Potential limitations of our research included: use of a small sample size, time constraints which led to an incomplete data set, and equipment malfunction.
An article that appeared in JASS, issue 2015
Keywords: aerobic; blood pressure; breathing; cardiovascular; color; exercise; recovery; senses; visual